Internet of Things (IoT): the role of an information literacy skills - Kamaruddin, Faten Elina; Ishak, Isma; Md Ajis, Ahmad Fuzi (Universiti Teknologi MARA, Johor, 2025)
The Internet of Things (IoT) is a gigantic network of appliances, sensors, and digital systems that can collect, send, and process data with little help from people (TechTarget, 2025). As IoT applications grow from traditional ways to automation, the amount, variety, and speed of data collection have all grown by a huge amount. So, in this case, information literacy has become very important since it is the basis for people and groups to find their way around, understand, and critically assess information in environments with a lot of sensors and tools available nowadays.